Null subjects in Slavic and Finno-Ugric licensing, structure and typology - Dalmi, Grete; Tsedryk, Egor; Ceglowski, Piotr (Studies in generative grammar., 2022)
The architecture of the human language faculty has been one of the main foci of the linguistic research of the last half century. This branch of linguistics, broadly known as Generative Grammar, is concerned with the formulation of explanatory formal accounts of linguistic phenomena with the ulterior goal of gaining insight into the properties of the 'language organ'. The series comprises high quality monographs and collected volumes that address such issues. The topics in this series range from phonology to semantics, from syntax to information structure, from mathematical linguistics to stud.